Recent Results from MINER nu A - Fields, L (2017)
The MINERνA collaboration is currently engaged in a broad program of neutrinonucleus interaction measurements. Several recent measurements of interest to the acceleratorbased oscillation community are presented. These include measurements of quasi-elastic scattering, diffractive pion production, kaon production and comparisons of interaction cross sections across nuclei. A new measurement of the NuMI neutrino beam flux that incorporates both external hadro-production data and MINERνA detector data is also presented.